Analysis of Capital Market Anomalies on the Indonesian Stock Exchange - Ratih Paramitasari (Green Publisher Indonesia, 2026)
The capital market plays a key role in disbursing funds from those who have a surplus to those who need financing, thereby supporting modern economic activities. This study aims to test the existence of market anomalies in the form of Monday Effect, Weekend Effect, and Rogalski Effect on the Indonesia Stock Exchange using a sample of companies in the LQ45 category during the period 2019–2025. The results showed that there was no significant difference between Monday's stock returns and other days, as well as between Friday's returns and other days, so the Monday Effect and Weekend Effect were not proven. The results of this study also showed that there was no significant difference in return between months, so the Rogalski Effect was also not found. These findings indicate that the Indonesian capital market tends to be efficient and does not show a systematic pattern of return based on trading days or months, so that investment strategies based on calendar anomalies are no longer relevant to obtain abnormal returns.